Faktor-Faktor Yang Berhubungan Dengan Pemberian ASI Eksklusif - Novia, Elmi (Jurnal Ilmu Gizi Indonesia (JIGZI), 2020)
Abstract The Ministry of Health has set an Exclusive Breastfeeding coverage target of 80 percent. In fact, only 27.5 percent of mothers in Indonesia are successful in giving exclusive breastfeeding. The annual report of Kabupaten Sijunjung Health Office covers exclusive breastfeeding coverage of 75.5% while the expected target is 80%. The purpose of this study was to determine the factors associated with exclusive breastfeeding in the working area of Tanjung Gadang Public Health Center Sijunjung District. The type of descriptive analytic research using approach is cross sectional. The population is targeted for mothers with babies> 6 months to 1 year. Sampling technique in this research is accidental sampling that is counted 81 people. Univariate data processing with frequency distribution and bivariate using computerized Chi Square analysis. Univariate results found more than half of respondents have low knowledge (63%). More than half of respondents had negative attitudes (54.3%). More than partially positive family support (50.6%). More than half of respondents have negative culture (58%). More than half of the respondents did not give exclusive breastfeeding to their babies (60.5%). There is a significant relationship between knowledge and exclusive breastfeeding (p value 0.001). There was a significant relationship between attitude and exclusive breastfeeding (p value 0,001). There was a significant relationship between family support and exclusive breastfeeding (p value 0,004). There was a significant relationship between culture and exclusive breastfeeding (p value 0.001). Keywords : Knowledge, Attitude, Family Support, Culture, Exclusive Breastfeeding